Input file for isolation-with-migration analysis of common voles, Microtus arvalis - Searle, Jeremy; Martínková, Natália; Barnett, Ross; Cucchi, Thomas; Struchen, Rahel; Pascal, Marine; Pascal, Michel; Fischer, Martin; Higham, Thomas; Brace, Selina; Ho, Simon; Quere, Jean-Pierre; et al. (Dryad Digital Repository, 2013)
The file contains mitochondrial cytb sequences and microsatellite genotypes of common voles formatted for the IMa program. Samples are labelled with isolate number.